Cap-dependent translational inhibition establishes two opposing morphogen gradients in Drosophila embryos. - Cho, P.F.; Gamberi, C.; Cho-Park, Y.A.; Cho-Park, I.B.; Lasko, P.; Sonenberg, N. (Current Biology, 2006)
In the early Drosophila embryo, asymmetric distribution of transcription factors, established as a consequence of translational control of their maternally derived mRNAs, initiates pattern formation . For instance, translation of the uniformly distributed maternal hunchback (hb) mRNA is inhibited at the posterior to form an anterior-to-posterior protein concentration gradient along the longitudinal axis . Inhibition of hb mRNA translation requires an mRNP complex (the NRE complex), which consists of Nanos (Nos), Pumilio (Pum), and Brain tumor (Brat) proteins, and the Nos responsive element (NRE) present in the 3' UTR of hb mRNA . The identity of the mRNA 5' effector protein that is responsible for this translational inhibition remained elusive. Here we show that d4EHP, a cap binding protein that represses caudal (cad) mRNA translation , also inhibits hb mRNA translation by interacting simultaneously with the mRNA 5' cap structure (m(7)GpppN, where N is any nucleotide) and Brat. Thus, by regulating Cad and Hb expression, d4EHP plays a key role in establishing anterior-posterior axis polarity in the Drosophila embryo.